Development of additional magnetron discharge in the drift region of an ion source with closed electron drift - Bordenjuk, I.V.; Panchenko, O.A.; Sologub, S.V.; Brown, I.G. (Вопросы атомной науки и техники, 2008)
A gas discharge of the magnetron type which is formed in the beam drift region of an ion source with closed electron drift was investigated. The electric field due to the target bias potential results in the development of an additional gas discharge of the magnetron type in the drift region. Trajectories of electron beams emitted by the ion source were visualized using light emission from the working gas excited by the electrons.